(M, β)-Stability of Positive Linear Systems. (23rd February 2016) - Pastravanu, Octavian; Matcovschi, Mihaela-Hanako
Abstract : The main purpose of this work is to show that the Perron-Frobenius eigenstructure of a positive linear system is involved not only in the characterization of long-term behavior (for which well-known results are available) but also in the characterization of short-term or transient behavior. We address the analysis of the short-term behavior by the help of the "( M, β ) -stability" concept introduced in literature for general classes of dynamics. Our paper exploits this concept relative to Hölder vectorp -norms, 1 ≤ p ≤ ∞, adequately weighted by scaling operators, focusing on positive linear systems. Given an asymptotically stable positive linear system, for each1 ≤ p ≤ ∞, we prove the existence of a scaling operator (built from the right and left Perron-Frobenius eigenvectors, with concrete expressions depending onp ) that ensures the best possible values for the parametersM andβ, corresponding to an "ideal" short-term (transient) behavior. We provide results that cover both discrete- and continuous-time dynamics. Our analysis also captures the differences between the cases where the system dynamics is defined by matrices irreducible and reducible, respectively. The theoretical developments are applied to the practical study of the short-term behavior for two positive linear systems already discussed in literature by other authors.